Rediscovering Chara as a model organism for molecular and evo-devo studies - Kurtović, Katarina; Schmidt, Vojtěch; Nehasilová, Martina; Vosolsobě, Stanislav; Petrášek, Jan (Protoplasma, 2024)
Chara has been used as a model for decades in the field of plant physiology, enabling the investigation of fundamental physiological processes. In electrophysiological studies, Chara has been utilized thanks to its large internodal cells that can be easily manipulated. Additionally, Chara played a pioneering role in elucidating the presence and function of the cytoskeleton in cytoplasmic streaming, predating similar findings in terrestrial plants. Its representation considerably declined following the establishment and routine application of genetic transformation techniques in Arabidopsis. Nevertheless, the recent surge in evo-devo studies can be attributed to the whole genome sequencing of the Chara braunii, which has shed light on ancestral traits prevalent in land plants. Surprisingly, the Chara braunii genome encompasses numerous genes that were previously regarded as exclusive to land plants, suggesting their acquisition prior to the colonization of terrestrial habitats. This review summarizes the established methods used to study Chara, while incorporating recent molecular data, to showcase its renewed importance as a model organism in advancing plant evolutionary developmental biology.
Keywords: Plants; Charophytes; Plant evolution; Biological Evolution; Cytoplasmic Streaming; Chara; Embryophyta; vyšší rostliny; proudění cytoplazmy; biologická evoluce; rostliny; Model plants